Tinjauan Kriminologi Terhadap Tindak Pidana Pengedaran Sediaan Farmasi Tanpa Izin Edar - Tommy Leonard; Kartina Pakpahan; Agnes Theresia Br Barus; Thomson Sukamto Marzuky Simatupang (UNIVERSITAS PGRI YOGYAKARTA, 2022)
Punishment is a form of deviation of behavior within society. One of the criminal acts in the field of pharmacy is related to the circulation of pharmaceutical preparations without an edar license, such as drug circulation without a edar licence that can harm society. The purpose of the research is to analyze the arrangements regarding the distribution of pharmaceutical preparations without authorization, efforts to combat such crimes, as well as the punishment given to the perpetrators. This research uses a method of research jurisprudence normative law, descriptive analysis using library data through libraries, regulations-legislation related to pharmaceutical preparations without authorization. The results of the criminal investigation of distributing pharmaceutical preparations without an edar license are regulated in Article 106 paragraph 1 junto 197 of the Law No. 36 of 2009 on Health. Procurement of pharmaceutical supplies is carried out by the pharmacy in the production, distribution and distribution facilities and facilities of pharmacy services. (pasal 6 PP Nomor 51 Tahun 2009 tentang pekerjaan kefarmasian). Countermeasures for criminal acts are carried out with penal and non-penal efforts. The punishment given is 4 (four) months and a fine of IDR 1,000,000.00 (one million rupiah) subsidiary of 1 (one) month in prison